Downregulation of EB1 impedes Cx43 localization and cardiac conduction after hypothermic ischemia-reperfusion in rats - Chunlei Wen; Rongfeng Yang; Jing Yi; Ying Cao; Yuting Song; Li An; Zijun Wang; Hong Gao (PeerJ)
Background Hypothermic ischemia-reperfusion arrhythmia is a common complication after cardiopulmonary bypass heart surgery, which can lead to hemodynamic disorders and even sudden cardiac death and is still not effectively prevented. This study aims to investigate the role and mechanisms of EB1 in hypothermic ischemia-reperfusion arrhythmia. Methods 4–6 week old male Sprague-Dawley (SD) rats were randomly assigned to four groups with a control group receiving no treatment. In the treatment groups, the rats received an injection of a negative control adenovirus (AAV9-CON) or an adenoviral vector containing Mapre1 gene (AAV9-EB1) or an equal volume of saline via the tail vein. After 4 weeks, untreated rat hearts underwent continuous isolated heart perfusion for 5 min, while the treatment groups were subjected to Langendorff isolated heart ischemia-reperfusion. The multi-electrode array (MEA) technique was used to measure the conduction heterogeneity of rat heart, evaluating the protective effects of EB1 overexpression against reperfusion arrhythmias. Additionally, histological staining and western blotting were used to explore the potential pathways by which EB1 exerts its anti-arrhythmic effects, potentially through promoting the localization of connexin 43 (Cx43) to the intercalated discs (IDs). Furthermore, western blot analysis was conducted to assess microtubule stability and evaluate the possible mechanism by which EB1 facilitates the localization of Cx43 to the IDs. Results Following ischemia-reperfusion, EB1 expression was downregulated, accompanied by a reduction in Cx43. Overexpression of myocardial EB1 reduced the incidence of reperfusion arrhythmias and shortened their duration, which was associated with improved myocardial conduction. Male SD rats injected with AAV overexpressing EB1 had significantly higher levels of both total myocardial Cx43 and gap junction Cx43 after ischemia-reperfusion compared to the non-overexpression groups. Histological staining revealed lateralization of Cx43 in ischemia-reperfusion myocardium, which was corrected by EB1 overexpression. Additionally, EB1 overexpression increased the distribution of Cx43 at the IDs, overall reducing Cx43 remodeling. Moreover, EB1 overexpression can also alleviate microtubule damage caused by ischemia-reperfusion, which may be an important mechanism for the transport of Cx43 to the IDs. Conclusions EB1 downregulation following hypothermic ischemia-reperfusion was accompanied by a reduction in gap junction Cx43. EB1 overexpression improved cardiac conduction and reduced reperfusion arrhythmias by promoting Cx43 localization to IDs, facilitating gap junctions (GJs) formation. These findings contribute to the development of new therapeutic targets for reperfusion arrhythmias.